1996
DOI: 10.1063/1.117364
|View full text |Cite
|
Sign up to set email alerts
|

Formation of quasicrystals in bulk glass forming Zr–Cu–Ni–Al alloys

Abstract: Zr65Cu17.5Ni10Al7.5 as well as Zr69.5Cu12Ni11Al7.5 belong to the best glass forming alloys known. Glass transition temperatures of melt-spun ribbons are 372 and 360 °C, respectively. TEM and x-ray analysis of samples annealed above the glass transition temperature exhibit the formation of quasicrystalline microstructures with small amounts of crystalline phases. The metastable icosahedral phase is primitive with a quasilattice constant a=0.253 nm; its composition as determined by EDX is close to Zr69.5Cu12Ni11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(170 citation statements)
references
References 1 publication
2
164
0
4
Order By: Relevance
“…Then, the question whether the ISRO is also able to quasicrystallize into I-phase is raised naturally. In view of the fact that the ISRO directly quasicrystallized into I-phase as the primary phase during solidification of Zr 39.5 Ti 39.5 Ni 21 melts and I-phase was observed frequently during primary crystallization of Zr-based MGs, 18,21,22 it is supposed that I-phase should be involved in the primary phases during crystallization of the Zr 65 Ti 10 Ni 25 MG. In order to confirm this assumption, a careful survey based on HRTEM experiments was conducted.…”
Section: -2mentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the question whether the ISRO is also able to quasicrystallize into I-phase is raised naturally. In view of the fact that the ISRO directly quasicrystallized into I-phase as the primary phase during solidification of Zr 39.5 Ti 39.5 Ni 21 melts and I-phase was observed frequently during primary crystallization of Zr-based MGs, 18,21,22 it is supposed that I-phase should be involved in the primary phases during crystallization of the Zr 65 Ti 10 Ni 25 MG. In order to confirm this assumption, a careful survey based on HRTEM experiments was conducted.…”
Section: -2mentioning
confidence: 99%
“…In previous reports, 21,22,34,35 the primary phase includes only one metastable phase, either an fcc crystalline phase or an I-phase, precipitated from amorphous matrix. Eckert et al 20 found that the metastable I-phase and fcc-Zr 2 Ni-type phase can be formed simultaneously as primary phases during crystallization of Zr 65 Al 7.5 Cu 17.5 Ni 10 MG when the alloy contains a certain amount of oxygen, indicating that the primary phase is sensitive to oxygen content of the materials.…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recently, quasicrystals were observed by crystallization of multicomponent alloy systems, such as ZrCuAl, ZrCuNiAl, ZrCuAlPd, ZrTiCuNiAl, and ZrAlNiCuAg amorphous alloys. [6][7][8][9][10] Such systems have a high glass forming ability and are stable against crystallization for long times in the temperature range of the supercooled liquid above the glass transition. They can be produced in the form of metallic bulk glasses.…”
Section: ͓S0003-6951͑00͒00949-9͔mentioning
confidence: 99%
“…For example, for heating rates of р10 K/min, the MA sample behavior merges with that for the liquid-quenched sample indicating a similar relaxation state. Indeed, at the merging point of 10 K/min, which corresponds to a characteristic time of about 10 2 s, the reported diffusivity in amorphous Zr-Al-Cu-Ni alloys (10 Ϫ19 -10 Ϫ20 m 2 /s) 15 implies a diffusional distance comparable to the nearest-neighbor separation ͑i.e., 0.3 nm͒. For heating ranges Ͼ10 K/min, the relaxation scales of the samples diverge.…”
mentioning
confidence: 99%